Ochrona praw człowieka a kryzys migracyjny w Europie. Zarys problematyki - Stępniak, Kamil (Kwartalnik Prawa Publicznego, 2016)
Migration movements have always led to demographic change and as a result also to civilization changes. The phenomenon of migration to the European Union that is currently taking place is not comparable in modern European history. Lack of coherent European Union policy leads to uncontrolled influx of immigrants. It is well known that economic migrants, and even criminals, are also emerging among Europe’s refugees. The lack of common legal and border protection measures in the Schengen area only deepens the existing crisis. The current influx of immigrants, when left uncontrolled, will endanger the public order of the EU. On the other hand, the provision of humanitarian aid and respect for human rights is deeply rooted in the European legal culture. The right question is therefore how to find a golden means to protect human rights while protecting the rights and freedoms of the people of the Old Continent. The European Union must face the enormous challenge of distinguishing refugees from terrorists and economic immigrants. This is of paramount importance to maintaining international peace and security. This task is put before both international bodies and legislation - both national, European and international. The respect for human rights is of paramount importance for the border protection and possible asylum procedure. It can not be forgotten that in spite of the need to reduce migration flows to EU territory, the whole procedure must be carried out in accordance with international human rights standards. This article is dedicated to selected issues of human rights protection in the context of the immigration crisis. Its purpose is to show the regulation of international human rights conventions, and in particular the European Convention on Human Rights as a tool which, on the one hand, ensures the protection of human rights and their fundamental values. On the other hand, it does not contradict the movement of migrants. The EU Court of Justice has consistently stated in its case law that the national authorities have a sovereign right to decide whether or not a foreigner may be admitted to or residing in the territory. This decision, however, can not affect the level of human rights protection.